A case of fulminant pneumococcus meningoencephalitis progressing with white matter involvement despite two doses of conjugated pneumococcus vaccine - Azapağası, Ebru; Kendirli, Tanıl; Tuncer, Gökçen Öz; Özcan, Serhan; Özdemir, Halil; Fitöz, Suat; İnce, Erdal (The Turkish Journal of Pediatrics, 2020)
Background. Streptococcus pneumonia is a cause of serious mortality and morbidity, especially among small children. However, currently, it causes lower rates of invasive infections due to successful vaccination programs Case. We report an exceptional case of a 6-month-old child with meningoencephalitis caused by Streptococcus pneumonia despite the administration of two doses of pneumococcal conjugate vaccine (PCV). Meningitis progressed rapidly and led to widespread damage in parenchymal brain tissue with the emergence of fulminant meningoencephalitis. Computed tomography (CT) and magnetic resonance imaging (MRI) revealed widespread brain lesions, suggesting extensive parenchymal injury. Conclusion. Such diffuse white matter lesions among pediatric patients with Streptococcus pneumonia meningoencephalitis despite two doses of PCV have not been reported previously.
Keywords: meningitis; meningoencephalitis; pneumococcal conjugate vaccine; serotype 19F; streptococcus pneumoniae